2018
DOI: 10.1136/bmjopen-2017-020162
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of wireless monitoring using a wearable patch sensor in high-risk surgical patients at a step-down unit in the Netherlands: a clinical validation study

Abstract: Background and objectivesIntermittent vital signs measurements are the current standard on hospital wards, typically recorded once every 8 hours. Early signs of deterioration may therefore be missed. Recent innovations have resulted in ‘wearable’ sensors, which may capture patient deterioration at an earlier stage. The objective of this study was to determine whether a wireless ‘patch’ sensor is able to reliably measure respiratory and heart rate continuously in high-risk surgical patients. The secondary objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
104
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(122 citation statements)
references
References 37 publications
10
104
2
Order By: Relevance
“…In line with previous data [9] we had more valuable data during the night-time, when patients are less mobile. A recent study exploring a similar patch type showed less accuracy of RespR between a wireless patch and a reference monitor [12]. However, the measurements with the patch showed much less intra-individual variability than measurements with the standard monitor, and thus it is possible that the reduced inaccuracy was due to the variability of RespR measurement by the reference monitor.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In line with previous data [9] we had more valuable data during the night-time, when patients are less mobile. A recent study exploring a similar patch type showed less accuracy of RespR between a wireless patch and a reference monitor [12]. However, the measurements with the patch showed much less intra-individual variability than measurements with the standard monitor, and thus it is possible that the reduced inaccuracy was due to the variability of RespR measurement by the reference monitor.…”
Section: Discussionmentioning
confidence: 95%
“…However, it has been shown previously that the SensiumVitals® patch reliably measured RespR when compared to a standard approach (e.g., counting RespR for a random 60 s interval during a 5 min period in a quietly breathing patient who is blinded to measurement period) [32]. In addition, the new wireless systems might be even more accurate than currently used reference methods, making prudent interpretation of received data necessary [12]. Notifications of incorrect measurements may result in false alarms, increasing workload of nurses and finally leading to alarm fatigue [45], with subsequent failure of the whole response system [46].…”
Section: Discussionmentioning
confidence: 99%
“…The range of the BR varies with age, weight, exercise tolerance, and body conditions, but the normal range at rest is between 12-20 breaths/min for adults [1]. During normal breathing, the BR is sometimes called eupnea while breathing abnormality occurs when BR falls outside the normal range and it can be classified into several events; tachypnea (a medical condition that occurs when BR exceeds the normal range), bradypnea (a medical condition occurs when BR is lower than the normal range), and central apnea (a medical condition occurs when there is no breathing for more than 10 s) [51,55].…”
Section: Anatomy Of the Respiratory System And Abnormalitymentioning
confidence: 99%
“…These devices could provide more frequent monitoring to detect deterioration earlier and avoid failures to rescue. 8 Increased awareness of patients' low activity or poor sleep may prompt interventions to improve these parameters, potentially reduce rehospitalizations and ultimately help reintegrate patients into the community.…”
Section: Introductionmentioning
confidence: 99%